2011
DOI: 10.1016/j.athoracsur.2010.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Center Variation in Patient Age and Weight at Fontan Operation and Impact on Postoperative Outcomes

Abstract: Background The impact of age and weight on outcomes following the Fontan operation is unclear. Previous analyses have suggested that lower weight-for-age z-score is an important predictor of poor outcome in patients undergoing bidirectional Glenn. We evaluated variation in age, weight, and weight-for-age z-score at Fontan across institutions, and the impact of these variables on post-operative morbidity and mortality. Methods Patients in the Society of Thoracic Surgeons Congenital Heart Surgery Database unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…Underweight status has been shown to predict outcomes in a variety of critically ill pediatric populations [2022]. In a recent study of PICU admissions at a tertiary referral center in the U.K., mean weight for age was significantly lower than that of the national reference population [10].…”
Section: Discussionmentioning
confidence: 99%
“…Underweight status has been shown to predict outcomes in a variety of critically ill pediatric populations [2022]. In a recent study of PICU admissions at a tertiary referral center in the U.K., mean weight for age was significantly lower than that of the national reference population [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patient weight in our cohort (13.2 kg) was far lower than the average of our historical Fontan patients (15 kg), and recent data has correlated low weight-for-age with increased morbidity and longer hospital stays. 14,15 Perhaps most concerning is the occlusion of the left limb in patient 5. By dividing the IVC flow between 2 limbs, reduced flow occurs in both.…”
Section: Discussionmentioning
confidence: 98%
“…40 Further, in a population of children after Fontan surgery demonstrated that Z-score of less than -2 was significantly associated with mortality, surgical failure, and length of hospital stay. 41 Nutritional status calculated by weight for age formula and young age were correlated with length of stay and hemodynamic status after a Glenn bidirectional surgery. 42 While accompanied with hypoalbuminemia, a poor nutrition in children with congenital heart disease increased the risk of mortality and postsurgical infections as well as prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in early corrective cardiac surgery has been resulted in a high mortality and morbidity rate. 6 A three years study (1991)(1992)(1993)(1994) at the Southampton University Hospital, United Kingdom, demonstrated a 4.4% post cardiac surgery mortality rate (<30 days). This rate was even higher (18%) when the procedure was performed in emergency setting, 7 and 29% when performed in a younger age population (i.e.…”
Section: Medical Journal Of Indonesiamentioning
confidence: 99%